Occurrence of mycotoxins in swine feed from South Korea - Jin, Wen; Park, Soo Yeon; Kim, Yo Han; Kim, Sung Jae; Han, Jeong Hee (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: To update recent information on contamination levels of mycotoxins in South Korea. Materials and methods: A total of 208 samples sourced from the feeds of swine farms were collected. The contamination levels of mycotoxins, which are aflatoxin (Afla), ochratoxin A (OTA), deoxynivalenol (DON), zearalenone (ZEN), fumonisin (FUM), and T-2 toxin, were investigated by enzyme-linked immunosorbent assays (ELISAs). Results: The detection levels of the total samples were 78.91% for DON, 75.24% for Afla, 47.02% for ZEN, 68.31% for FUM, and 5.94% for OTA and T-2, which were not detected at all. Most of the analyzed mycotoxins showed significant high occurrences in 47.02%–78.91% of the swine feed samples. 11 of the 152 alfa-positive samples exceeded the maximum residue limit (MRL) of Afla proposed by the Korean regulation. In the analysis of mycotoxin detection levels by growth stage, ZEN was found in the nursery stage at a remarkably high concentration level (126.46 ± 63.76 ppb), exceeding the MRL of ZEN for piglets proposed by the European Commission. This mycotoxin was also found in the samples from the gestation barn (89.04 ± 46.05 ppb) and the farrowing house (105.58 ± 94.12) at a high concentration level. Afla was found in the nursery stage at a high concentration (8.00 ± 2.22 ppb), approaching the MRL (10 ppb) of Afla proposed by the Korean regulation. Conclusion: These results indicate that many swine farms in South Korea are still exposed to mycotoxin risk, and special attention and surveillance are necessary for these mycotoxin risks in swine farms. Adv. Vet. Anim. Res., 11(1): 125-131, March 2024 http://doi.org/10.5455/javar.2024.k756